Clinical Characteristics and Quality of Life in a Cohort of Polish Pediatric Patients with Hereditary Angioedema - Katarzyna Piotrowicz-Wójcik; Malgorzata Bulanda; Ewa Czarnobilska; Grzegorz Porebski (MDPI AG, 2024)
Hereditary angioedema (HAE) is a rare genetic disease. It is characterized by recurrent attacks of angioedema. Evidence to what extent it affects patient functioning is limited in the pediatric population. We aimed to determine the clinical characteristics and management of Polish children with HAE and to measure the health-related quality of life (HRQoL) of these patients. This cross-sectional study was conducted among 21 pediatric patients and their caregivers, as well as 21 respective controls randomly selected from the general population. During routine follow-up visits, standardized pediatric quality of life questionnaires (PedsQLTM 4.0) were administered to all caregivers and adolescents (≥13 years). Caregivers also completed a structured medical interview regarding the clinical characteristics and treatment of children with HAE during the previous six months. During this period, 57% of patients had low (group I), 24% moderate (group II), and 19% high (group III) HAE activity, corresponding to ≥10 attacks per 6 months. None of the patients received long-term prophylaxis. The children in group III had a lower HRQoL than other groups and controls on all dimensions of the PedsQLTM 4.0. The lowest scores in all groups were observed in the emotional functioning domain. Our data demonstrate that the burden of HAE on the quality of life of pediatric patients and their families encompasses a wide range of daily functioning.